Elevated serum tumour necrosis factor‐like weak inducer of apoptosis in alopecia areata: a possible marker of disease severity. (12th November 2019) - Sayed, K.; Mohammed, F.; Abdel Hay, R.; Ezzeldin, N.; Rashed, L.; Fahim, A.
Summary: Background: Alopecia areata (AA) is, an organ‐specific autoimmune disease, characterized by an aberrant expression of cytokines of the T helper 1 type. Tumour necrosis factor‐like weak inducer of apoptosis (TWEAK) is a multifactorial cytokine that exerts a role in the pathogenesis of inflammatory and autoimmune diseases, especially in cutaneous diseases. Aim: To estimate the serum level of TWEAK in AA and to correlate it with different parameters. Methods: This case–control study enrolled 40 patients with AA and 50 clinically healthy volunteers matched for age and sex. A blood sample (5 mL) was extracted from each participant for analysis of serum TWEAK levels by ELISA. Results: Levels of TWEAK were significantly higher in patients with AA (mean ± SD 213.7 ± 59.2 pg/mL, range 109.1–341.6 pg/mL) than in controls (95.97 ± 13.28 pg/mL, range 80.1–152.3 pg/mL) ( P < 0.001). A significant positive correlation was found between serum TWEAK level and the Severity of Alopecia Tool (SALT) score ( r = 0.56, P < 0.001). Conclusion: To our knowledge, this study highlights for the first time a possible link between higher serum TWEAK level and AA. Serum TWEAK level appears to reflect AA disease severity.